SENI SUARA DAERAH SEBAGAI MEDIA PENDIDIKAN APRESIASI SENI - Isti Kurniatun (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2004)
This research 'on the art of Javanse singing as education ill art  appreciation thought in Elementary Schools ill Surakarta aims to discover  all incongruity between. the goals of the Local Curriculum and its  implementation. The incongruity can be found until the recent time, and  therefore the goals of the Local Curriculum, which is perserving national  culture totally unsucceeds. The art observers, academics and relevant  institution have to react concretly to anticipate these konditions in order  to succeed the goals of the Local Curriculum.Key words: Javanese singing, education, art appreciation, Elementery Schools